Surgical Repair of Proximal Hamstring Tendon Avulsion - Falotico, Guilherme Guadagnini; Scatigna, Bruno Francesco (Revista Brasileira de Ortopedia, 2025)
Injuries to the proximal hamstring muscle complex are common in athletes and range from strains to tendinous and bony avulsions. The lesion mechanism typically involves an eccentric contraction of the hamstring muscles during abrupt hip hyperflexion with the knee in extension. Low-speed injuries occur in high kicks and splits, whereas tendon avulsions are common in high-speed activities, such as running and ballet. Clinically, patients present with pain, subcutaneous hematoma, and, sometimes, a palpable defect. Additional signs include limited knee extension and involvement of the sciatic nerve. Diagnosis relies on ultrasonography, magnetic resonance imaging (MRI), and radiography, and MRI is the standard test. Surgical treatment is indicated for complete avulsions, especially in athletes, to prevent loss of strength and difficulty in returning to sports. In the surgical technique herein described, we perform one or two transverse incisions in the gluteal fold, depending on the tendon retraction, followed by fixation with metal anchors. The postoperative period includes initial restriction, followed by accelerated rehabilitation for return to sports by the twelfth week. Since 2019, the technique has been applied to 13 patients, demonstrating good outcomes, without re-ruptures and a postoperative Tegner score similar to the preoperative one.
Keywords: hamstring muscle; hamstring tendons; tendon injury